Applicability of new sustainable and efficient green metal-based nanoparticles for removal of Cr(VI): Adsorption anti-microbial, and DFT studies. (1st March 2023) - Singh, Simranjeet; Naik, T.S.S.K.; Thamaraiselvan, C.; Behera, S.K.; N, Pavithra.; Nath, Bidisha; Dwivedi, P.; Singh, Joginder; Ramamurthy, Praveen C.
Abstract: Artemisia absinthium leaves were utilized as a reducing agent for green synthesis of Zinc oxide nanoparticles (particle size 17 nm). Synthesized green-ZnO (g-ZnO) were characterized by SEM/EDX, FTIR, XRD, UV, and BET analyses and then further used as an adsorbent to remove Cr(VI) ions from simulated wastewater. Optimal pH, temperature and adsorbent dosage were determined through batch mode studies. High removal efficiency and adsorption capacity were observed at pH 4, 0.25 g L −1 dosage, and 25 mg L −1 concentration of Cr(VI). Experimental data were modelled with different adsorption kinetics (Elovich model, PFO, PSO, IDP model) and isotherms (Langmuir, Freundlich, and Temkin), and it was found the adsorption process was well fitted to Langmuir with an R 2 value greater than>0.99. Computational calculation showed that the g-ZnO nanoparticles became ∼14 times more dynamic with delocalized surface states making them a relevant platform to adsorb Cr with greater work function compatibility supporting the experimental findings. The Qmax adsorption capacity of g-ZnO was 315.46 mg g −1 from Langmuir calculations. Thermodynamic calculations reveal that the Cr (VI) adsorption process was spontaneous and endothermic, with a positive ΔS value representing the disorder at the solid-solution interface during the adsorption. In addition, the present study has demonstrated that these g-ZnO nanoparticles show strong antibacterial activities against P. aeruginosa (MTCC 1688) and E. coli (MTCC 1687). Also, the novel g-ZnO adsorbent capacity to remove Cr(VI) from simulated water revealed that it could be reused at least six times with higher removal rates during regeneration experiments. The results obtained from adsorption and antimicrobial activities suggest that g-ZnO nanoparticles could be used effectively in real-time wastewater and agricultural safety applications. Graphical abstract: Image 1 Highlights: Synthesis of ZnO nanoparticles by a green method using leaves of Artemisia absinthium . Material Characterizations performed to explain structural aspects and functionality. ZnO nanoparticles exhibited removal efficiencies for Cr(VI) from an aqueous matrix. Desirable operating conditions for ZnO for adsorption of Cr(VI) were determined. Pseudo-second-order kinetics and Langmuir validated the performance with Qmax of 315.46 mg g −1